2022
DOI: 10.21203/rs.3.rs-1843732/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monoclonal Antibodies Against CGRP (R): Non-responders and Switchers: Real World Data from a Large Case Series

Abstract: ObjectiveAssessement of the responder and non-responder rate to consecutive monoclonal CGRP-antibody (CGRP-mAb) treatment, the presence of side effects, analysis of predictors of response and loss of efficacy evaluation over time. Methods We conducted a retrospective analysis including 171 patients with episodic (EM) or chronic migraine (CM), who received one, two or three different CGRP-(R)-mAbs. Non-response was defined as ≤50% reduction of monthly migraine days (MMDs) in EM and ≤ 30% reduction of MMDs in CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…This is comparable to ≥ 50% response rates seen in patients on their second anti-CGRP(-R) mAb in some other studies, e.g. 42.8% (59/138) in a real world study with fremanezumab (Finesse) at three months [19], and 42.3% (11/26) in an Austrian case series [9]. Other studies with limited sample sizes reported lower ≥ 50% response rates after switching: 13.6% (3/22) In the group of patients with two switches, the ≥ 50% response rate and mean reduction in MHD and MMD at six months were distinctly lower, in particular during the third treatment cycle, while the baseline MHD and MMD were higher than in the other subgroups.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This is comparable to ≥ 50% response rates seen in patients on their second anti-CGRP(-R) mAb in some other studies, e.g. 42.8% (59/138) in a real world study with fremanezumab (Finesse) at three months [19], and 42.3% (11/26) in an Austrian case series [9]. Other studies with limited sample sizes reported lower ≥ 50% response rates after switching: 13.6% (3/22) In the group of patients with two switches, the ≥ 50% response rate and mean reduction in MHD and MMD at six months were distinctly lower, in particular during the third treatment cycle, while the baseline MHD and MMD were higher than in the other subgroups.…”
Section: Discussionsupporting
confidence: 82%
“…In real-world observational studies, the ≥ 50% response rates to anti-CGRP(-R) mAbs range from 50% to 70% depending on baseline patient characteristics and duration of therapy, leaving 30%-50% of patients not benefiting significantly from treatment. Accumulating recent reports of non-responders to anti-CGRP(-R) mAbs and switchers [6,8,9,18,19], highlight the fact that, while anti-CGRP(-R) mAbs are highly effective and well-tolerated medications, they are not the panacea patients sometimes hope for, and have relevant limitations. This could be due to alternative neuropeptides and signaling pathways involved in migraine pathogenesis playing a more crucial role in the non-responders [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation